[4+2] vs [3+2] Annulations in the Nickel‐ and Cobalt‐Catalyzed Reaction of ortho‐Haloimines with Alkynes: Differential Reactivity towards the Synthesis of Isoquinolines and Aminoindenes. Issue 1 (22nd October 2013) - Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract Metal‐catalyzed annulation reactions to synthesize carbo‐ and heterocycles have been an attractive field of research for many years. The development of new cyclization reactions utilizing readily available less expensive metal catalyst is one of the important tasks. In this regard, this review summerizes and discusses about nickel‐ and cobalt‐catalyzed [4+2] and [3+2] annulation reactions of ortho‐halo substituted imines and alkynes. Nickel complexes under suitable reaction conditions underwent [4+2] annulation to form six‐membered isoquinoline (salts) derivatives. However, cobalt complexes afforded aminoindenes via [3+2] annulation reactions. Both reactions proceed through a five membered metallacycle. The regioselective insertion of alkyne containing keto or ester groups into the metallacycle further demonstrates the difference in selectivity of these metal complexes.